Da’wah in international publications: Bibliometric analysis of scopus database - Hasan Albana (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2022)
Purpose - This study aims to determine the map of the development of publications and the description of the model of articles about da'wah published on Scopus.Method - This study uses a descriptive method with a bibliometric approach to determine the structure and dynamics of da'wah studies in Scopus publications in 2000-2022. There are five stages carried out in this study, namely determining keywords, searching for data, selecting and sorting articles, validating data, and analyzing data. This study uses the VOSviewer application to identify the relationship among journals, countries, and keywords related to da'wah.Result - The results of this study indicate that studies on da'wah published in Scopus-indexed journals are still relatively few, in 2000-2022, there were only 52 articles on da'wah published by Scopus. Journal of Communication: Malaysian Journal of Communication is the Scopus-indexed journal that publishes the most articles on da'wah. Don Abdul Ghafar is the author who publishes the most articles on da'wah on Scopus. The article entitled THE ART OF DAKWAH: Social Media, Visual Persuasion and The Islamist Propagation of Felix Siauw became the most cited article. Indonesia is the country that publishes the most articles on da'wah on Scopus and is the locus of studies on da'wah.Implication – This study suggests conducting a da'wah study that is still being studied, such as sustainable da'wah with the object of individual study and social change.Originality - This study is the first to examine the map of da'wah research in Scopus publications.***Tujuan - Penelitian ini bertujuan untuk mengetahui peta perkembangan publikasi dan gambaran model artikel tentang dakwah yang dipublikasikan di Scopus.Metode – Penelitian ini menggunakan metode deskriptif dengan pendekatan bibliometrik untuk mengetahui struktur dan dinamika kajian dakwah dalam publikasi Scopus tahun 2000-2022. Terdapat lima tahapan yang dilakukan dalam penelitian ini yaitu menentukan kata kunci, mencari data, memilih dan menyortir artikel, memvalidasi data, dan menganalisis data. Penelitian ini menggunakan aplikasi VOSviewer untuk mengidentifikasi hubungan antar jurnal, negara, dan kata kunci terkait dakwah.Hasil - Hasil penelitian ini menunjukkan bahwa kajian dakwah yang dipublikasikan di jurnal terindeks Scopus masih relatif sedikit, pada tahun 2000-2022 hanya terdapat 52 artikel dakwah yang diterbitkan Scopus. Jurnal Komunikasi: Jurnal Komunikasi Malaysia merupakan jurnal terindeks Scopus yang menerbitkan artikel dakwah terbanyak. Don Abdul Ghafar merupakan penulis yang paling banyak menerbitkan artikel dakwah di Scopus. Artikel berjudul SENI DAKWAH: Media Sosial, Persuasi Visual dan Dakwah Islamis Felix Siauw menjadi artikel yang paling banyak disitasi. Indonesia merupakan negara yang paling banyak menerbitkan artikel dakwah di Scopus dan menjadi lokus kajian dakwah.Implikasi – Kajian ini menyarankan untuk melakukan kajian dakwah yang masih terus dikaji, seperti dakwah yang berkelanjutan dengan objek kajian individu dan perubahan sosial.Orisinalitas - Kajian ini merupakan yang pertama mengkaji peta kajian dakwah dalam publikasi Scopus.